Extraction behaviour of Cu(II) and Fe(III) from chloride medium to the hydrophobic ionic liquids using 1,10-phenanthroline / Nurul Yani Rahim - Nurul Yani, Rahim (2011)
The study of liquid-liquid extraction of Cu(II) and Fe(III) ion was carried out using a series of hydrophobic ionic liquid; 1-butyl-3-methylimidazolium hexafluorophosphate ([C4mimPF6]), 1-hexyl-3-methylimidazolium hexafluorophospahate ([C6mimPF6]), 1-butyl-3-methylimidazolium bistrifluoromethylsulfonyl imide ([C4mimNTf2]) and 1-hexyl-3-methylimidazolium bistrifluoromethylsulfonyl imide ([C6mimNTf2]) as the extraction phase. Cu(II) showed a preferential extraction into less hydrophobic ionic liquid, [C4mimPF6]. The extraction behavior of Cu(II) ions depend on the type of counter ion present. The extraction process of Cu(II) ion in ionic liquid proceeded via similar mechanism to that of a molecular organic solvent. From the results obtained, an ion pair mechanism is proposed for the extraction of Cu complexes from chloride medium. Fe(III) favors extraction into [C6mimNTf2], the most hydrophobic ionic liquid. Anion exchange is the mode of extraction of Fe complexes from chloride medium.